Cassapro in broiler ration : effect of halquinol Supplementation - I.P Kompiang; A.P Sinurat; T Purwadaria; J Darma; Supriyati . (Indonesian Center for Animal Research and Development (ICARD), 1997)
A trial was conducted to determine the effect of various level of cassapro (fermented cassava) and halquinol supplementation on the performance of broiler chickens . Experimental rations were formulated isoprotein and isoenergy with graded level of cassapro (0, 10, 20 and 30%) . The 20 and 30% cassapro ration were prepared without and with halquinol supplementation (60 ppm). Each ration was fed to 40 of three day old broilers, divided into 4 cages ( 5 males and 5 females per cage) for 4 weeks. Increasing the level of cassapro significantly reduced body weight gain (P < 0.005), increased feed conversion ratio (FCR) (P < 0.0005) with no effect on feed intake (P < 0.10) . Halquinol supplementation has no effect on feed intake, but significantly increased body weight gain (P <0.05) and improved the FCR (P < 0.01) . It is concluded that high level of cassapro in the ration will cause poorer performance of the birds, however it can be alleviated by halquinolsupplementation. Keywords: Broiler, cassapro, halquinol